OPTIMASI PERFORMA JARINGAN WIRELESS MENGGUNAKAN METODE (HTB) HIERARCHICAL TOKEN BUCKET PADA UNIVERSITAS MUHAMMADIYAH MALUKU UTARA - Nova Kartika; Mustamin Hamid; Sahriar Hamzah (Pusat Riset dan Inovasi Nasional, 2022)
In wireless networks, the problem of weakening the signal mentioned above requires more serious attention, because considering that the data transmission medium by this wireless network uses broadcast air. The purpose of this study is to optimize and analyze network performance on the Wireless network on the third floor of building A UMMU and at the same time to compare the two methods to get the QOS value. In this study using 3 clients, the amount of bandwidth used is 10 MBps which is divided into 5 MBps, 3 MBps, and 2MBps assuming the bandwidth will be divided between each client using the HTB (Hierarchical Token Bucket) method. While the Action Research method to be able to determine network performance using QoS parameters, namely Diagnosis (Diagnosing), Action Planning (action planning), Taking Action (Action Taking), Evaluation (Evaluating), Learning (learning). The results of this study are that the delay in bandwidth management using the HTB queuing method is smaller than using the Action Research method, the second throughput in bandwidth management using HTB is smaller than the Action Research method and the browsing speed is faster when implementing the HTB bandwidth management method. While the Action Research Method is only able to evaluate the browsing speed of some network users. Based on the results above, it can be seen that the network quality using the HTB queuing method is more optimal, this is because the bandwidth will be divided according to the rules applied.